Young Adults and the Psychotic Disorders: A systematic review of Randomized Clinical Trials (RCTs), investigating the efficacy of Cognitive-Behavioral Therapy and Acceptance and Commitment Therapy - H. I. Mamo; T. Iliopoulou; P. Louka; V. Ladas (Dialogues in Clinical Neuroscience & Mental Health, 2022)
Psychotic symptoms, or episodes are mostly associated with chronic, severe, and treatment refractory adult schizophrenia cases, with a usual onset around 10 ± 2 years of age. The present systematic, qualitative analysis attempts to explore the effectiveness of Cognitive Behavioral Therapy (CBT) and Acceptance and commitment therapy (ACT) on psychosis-related symptoms in young adults. For the facilitation of this analysis, the most relevant Randomized Clinical Trials (RCTs) were chosen.A time frame from 2010 to present was applied regarding the effectiveness of CBT and ACT on young adults regarding Psychosis. CBT is a psycho-social intervenionarytool, aims to the improvement of mental health, focuses on challenges e.g. changing cognitive distortions and behaviors.ACT is a part of clinical behavior analysis, a type of psychotherapy, and it is an empirically supported psychological intervention that increases psychological flexibility by combining acceptance and mindfulness tactics with commitment and behavior-change strategies in various ways. Advantages emerged by the two analyzed interventions as well as methodological limitations across studies clearly defining the needs that must be fulfilled when attempting to manage the difficulties emerging in young adults within the psychotic spectrum.A combination of CBT and ACT may be powerful against psychosis, considering that cognitive transformation and mindful engagement, respectively, may give a strong tool for penetrating in psychotic mental states.